2013
DOI: 10.1038/hr.2013.30
|View full text |Cite
|
Sign up to set email alerts
|

Resistant hypertension and target organ damage

Abstract: Cardiovascular (CV) complications such as myocardial infarction, heart failure, stroke and renal failure are related to both the degree and the duration of blood pressure (BP) increase. Resistant hypertension (RH) is associated with a higher risk of CV complications and a higher prevalence of target organ damage (TOD). The relationship between CV disease and TOD can be bidirectional. Elevated BP in RH may cause CV structural and functional alterations, and the development or persistence of left ventricular hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 52 publications
2
43
0
4
Order By: Relevance
“…It has been demonstrated that patients with concentric hypertrophy have poorer outcomes than patients presenting normal LV geometry. 3,4 Resistant hypertension (RHTN) is of major clinical importance since it is associated with higher cardiovascular risk [5][6][7][8] which can be dependent on concentric hypertrophy. However, RHTN often coexists with obstructive sleep apnea (OSA) 9,10 and metabolic syndrome (MS), which also predispose to LVH.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that patients with concentric hypertrophy have poorer outcomes than patients presenting normal LV geometry. 3,4 Resistant hypertension (RHTN) is of major clinical importance since it is associated with higher cardiovascular risk [5][6][7][8] which can be dependent on concentric hypertrophy. However, RHTN often coexists with obstructive sleep apnea (OSA) 9,10 and metabolic syndrome (MS), which also predispose to LVH.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that PA patients have a higher incidence of cardiovascular complications than age-and sex-matched patients with essential hypertension [5]. Several studies have shown that PA is common in patients with resistant hypertension, with a prevalence of approximately 20% [6], and PA is associated with a significant increase in risk of end-organ damage and cardiovascular events compared with more easily controlled hypertension [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, some current therapeutic strategies appear to be of limited effectiveness for an increasing number of patients, with multidrug resistance or poor adherence to treatment regimes being reported (Morisky et al, 2008;Tomaszewski et al, 2014;Vega & Bisognano, 2014;Vongpatanasin, 2014;Sakhuja et al, 2015). Resistant hypertension is associated with increased target organ damage and cardiovascular complications (Muiesan et al, 2013). As such, and alongside likely increasing demand from an increasingly ageing global population, there is a pressing need for development of new and more effective strategies to prevent and treat hypertension.…”
Section: A Global Clinical Issuementioning
confidence: 99%